Adaptation strategy of farming communities in Renah Kayu Embun Village, Kumun Debai District, Sungai Penuh City - Agustin Wela Sasih (Priviet Social Sciences Journal, 2025)
The farming community in Renah Kayu Embun Village utilizes land for farming to meet their daily needs. However, they face several obstacles, including weather conditions, land slopes, limited equipment, and long distances to market. This requires the community to adapt to the conditions it faces. This study aims to describe and explain the adaptation strategies employed by the farming community to survive the conditions they face. Data collection methods included interviews, observation, and documentation.The research results show that there are several adaptation strategies carried out by farming communities: First, adaptation strategies to the natural environment; (1) Digging a well, (2) making a water reservoir, (3) carrying out the tradition of sending rain. (4) Convert sloping land into steps. Second, adaptation strategies to tool limitations include (1) making sungkaik and coffee grinders and (2) Usoh as a traditional means of transportation. Some of the adaptation strategies carried out by farming communities are in the form of ideas, knowledge, and culture that are formed as a result of long interactions with the natural and social environment.